2012
DOI: 10.5124/jkma.2012.55.11.1063
|View full text |Cite
|
Sign up to set email alerts
|

Work-related diseases of agricultural workers in South Korea

Abstract: 본 논문은 우리나라 농업인들의 농작업 관련한 주요 질병 A gricultural work involves many health hazards, and these can induce related health problems. However, because of low public concern and insufficient political support in the South Korean agricultural sector, agricultural health and safety is facing a serious crisis. The common work-related diseases of agricultural workers are the work-related musculoskeletal diseases like osteoarthritis of the hip and low back pain, skin diseases, pesticide poisoning, infectious and respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…According to the Human Development Report of the United Nations Development Programme, on a global scale, the daily work time of agricultural workers in Korea is long, and it is 10 hours 35 minutes for men and 11 hours 11 minutes for women. Thus, these long work hours of Korean agricultural workers, in addition to the year-round farming season, may support the results of the present study [27]. …”
Section: Discussionsupporting
confidence: 88%
“…According to the Human Development Report of the United Nations Development Programme, on a global scale, the daily work time of agricultural workers in Korea is long, and it is 10 hours 35 minutes for men and 11 hours 11 minutes for women. Thus, these long work hours of Korean agricultural workers, in addition to the year-round farming season, may support the results of the present study [27]. …”
Section: Discussionsupporting
confidence: 88%
“…Common work-related diseases of agricultural workers are work-related musculoskeletal diseases such as osteoarthritis of the hip and low back pain, skin diseases, pesticide poisoning, infectious and respiratory diseases, and effects of exposure to physical agents on health. For the most part, these health problems are related directly to agricultural work [41] . Mycobacterium abscessus infection of the hand was reported in two otherwise healthy fish handlers.…”
Section: Resultsmentioning
confidence: 99%
“…Hip-related MSDs have not been investigated in developing countries. However, in developed countries, it has been shown that there is a relationship of this disease with the driving tractors and agricultural machinery for a long period of time (South Korea and USA) [114,116].…”
Section: Msd Studies In Agriculturementioning
confidence: 99%
“…The prevention of MSDs and, consequently, the improvement in working conditions render agricultural operations (including livestock, fishing and forestry) more sustainable (India, Brazil, Colombia, Malaysia, Trinidad and Tobago, Iran, Thailand, Algeria, the Philippines, Finland, USA, the Netherlands, Germany, South Korea, Belgium, Portugal, Canada, Italy, France, Sweden, Spain, Poland and Greece) [24,58,87,89,104,107,110,111,114,118,121,124,126,127,140,142,146,148,159,175,184,194,201,209,226,.…”
Section: Msd Studies In Agriculturementioning
confidence: 99%
See 1 more Smart Citation